Learning Cultural Arts (Musik) in Class XI IPS SMA S PSM Bukittinggi - Pratama, Bima Eko; Hadi, Harisnal (Universitas Negeri Padang, 2024)
The research aims to describe how the Learning Process of Cultural Arts (Nusik) in Class XI IPS SMA S PSM Bukittinggi. The type in this research is qualitative using a descriptive method. The instruments in this study are the researcher himself and assisted by other instruments such as stationery, cameras and voice recorders. This research uses data collection techniques, namely observation, interviews, documentation and literature studies. The steps to analyze the data in this study are collecting data, identifying and inferring. The results obtained in the research conducted by researchers at SMA S PSM Bukittinggi, that there are 2 factors that affect the learning process in class XI IPS SMA S PSM Bukittinggi which include attention, learning readiness and student interest. Meanwhile, teacher factors include nusik art learning methods and media. Based on the discussion and conclusion of the research results, several suggestions were conveyed, including: to students to be more serious and focused in following the learning process of cultural arts (nusik). To teachers to use the methods and media that have been designed in the lesson plan so that learning is more interesting and not boring.